Fontes de formação de crenças de autoeficácia no trabalho de professores do ensino fundamental: associações com as dimensões de Burnout - VEIGA, Lyana Cristina Guzmán (2023)
Self-efficacy, as it forms the basis of motivation and influences human behavior, can have implications for teaching. Acting as a determinant of the persistence and achievement of goals, evidence shows positive associations between self-efficacy, personal fulfillment, well-being at work and negative with burnout. In this direction, the present study, inserted in the line of research "Training and action of the teaching professional and educational practices", aimed to verify the perception of the teachers in relation to the beliefs of self-efficacy, sociodemographic correlations and the sources of self-efficacy with the Burnout Syndrome, differences in the averages of the applied scales, as well as the prediction of the sources in the Burnout scores of elementary school teachers from public and private schools in a municipality and surrounding cities, in the interior of the western region of the state of São Paulo. To this end, two studies were carried out, the first being a scope review with searches in four databases: Virtual Health Library (BVS-Saúde), CAPES Periodical Portal, Institute of Education Sciences (ERIC) and National Library of Medicine (PubMed) from 2012 to 2022, observing the PRISMA-ScR recommendations. 17 studies were selected. The results showed that among the occupational factors that impact self-efficacy and burnout, time in the profession, types of feedback received, cooperation between peers and excessive work demands were listed. As for the intersections between self-efficacy and burnout, as a whole, teachers with low levels of self-efficacy may be more inclined to experience the dimensions of Burnout. The second contour study with the participation of 50 teachers from public and private elementary schools, 23 (46%) from a city in the interior of western São Paulo and 27 (54%) from surrounding municipalities, with 78% of the sample (N = 39) was female. The instruments were applied: Scale of Sources of Teaching Self-Efficacy and the Maslach Burnout Inventory (MBI), in addition to a sociodemographic questionnaire. Data collection took place exclusively online through the snowballing of a form link via Google Forms via the use of online social networks. As for the dimensions of burnout, the analyzed sample showed higher averages in professional fulfillment (M=31.74). Emotional exhaustion reached an intermediate mean (M=25.26), and depersonalization the lowest mean (M=6.08), not configuring classic Burnout scores in this population. Regarding self-efficacy, the highest score was related to the social persuasion source (M=25.4). Based on Pearson's correlation, it was found that depersonalization was moderately correlated with emotional exhaustion (0.561), while vicarious experience was correlated with professional achievement (0.307). It was also noted that physiological states correlated with emotional exhaustion (0.518) and with social persuasion (0.505). It is highlighted, in the set of data, the relevance of considering the subjective aspects of the teacher, suggesting the incentive to strengthen self-efficacy and well-being as a prevention of psychological illness and burnout.